2013
DOI: 10.1016/j.drugalcdep.2013.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Modeling longitudinal drinking data in clinical trials: An application to the COMBINE study

Abstract: Background There is a lack of consensus in the literature as to how to define drinking outcomes in clinical trials. Typically, separate statistical models are fit to assess treatment effects on a number of summary drinking measures. These summary measures do not capture the complexity of drinking behavior. We used the COMBINE Study to illustrate a statistical approach for examining treatment effects on high-resolution drinking data, which takes into account abstinence and non zero drinking in the same analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
0
10
1
Order By: Relevance
“…Naltrexone significantly decreases the risk of drinking, which is consistent with the original COMBINE report (where naltrexone reduced the number of drinks per day). The original report did not find an effect of naltrexone on abstinence; however, this was detected in the current paper (and in other reports that consider the longitudinal vector of drinking) because of the way abstinence is operationalized in the zero-inflated model 45 .…”
Section: Discussioncontrasting
confidence: 83%
“…Naltrexone significantly decreases the risk of drinking, which is consistent with the original COMBINE report (where naltrexone reduced the number of drinks per day). The original report did not find an effect of naltrexone on abstinence; however, this was detected in the current paper (and in other reports that consider the longitudinal vector of drinking) because of the way abstinence is operationalized in the zero-inflated model 45 .…”
Section: Discussioncontrasting
confidence: 83%
“…However, a zero-inflated model might still be useful if there are reasons to suspect two distinct processes that generate zero-observations. DeSantis et al (2013) found that a hurdle-Poisson model worked well to evaluate treatment effects from high-resolution drinking data. They also found that placing the hurdle at a "low-risk"-cutoff of 4 to 5 for the number of drinks per day, fit the data better than a hurdle at zero.…”
Section: Similar Problems In Other Research Fieldsmentioning
confidence: 99%
“…Wang et al (2002) discussed several basic methods for analysing drinking data (such as reducing the repeated measures of drinking over the whole study period to one summary for each subject, such as the proportion of drinking days or average alcohol consumption per day, and then analysing these univariate summaries, or using survival models to analyse time to the first (any or heavy) drinking day) and argued for the use of more sophisticated statistical methods (specifically, recurrent event survival analyses) that give a more comprehensive description of drinking behaviour over time. Other researchers (DeSantis et al, 2013;Zhu et al, 2017) proposed a longitudinal hurdle or zero-inflated Poisson model to analyse the zero-inflated average number of drinks per day (as opposed to the average number of drinks per drinking day) for each week (rounded to the nearest whole number). This artificially inflates the proportion of zeros by rounding and ignores the number of days in which drinking occurred during the week.…”
Section: Introductionmentioning
confidence: 99%
“…For subject B, who drinks heavily during the weekend (seven drinks on Saturday and seven on Sunday) and abstains for the rest of the week, we model the number of drinking days (2) and the average of seven drinks per drinking day. Previous literature using average drinks per day (DeSantis et al, 2013;Zhu et al, 2017) would solely model an average of 2 in both cases. Distinguishing between the two drinking patterns of subjects A and B is important because these two types of individual could have different future health and psychosocial outcomes, and treatments may be associated with different drinking patterns.…”
Section: Introductionmentioning
confidence: 99%